Performance Evaluation of Contract Labor Using Cluster Analysis - Putra, Putu Pasek Wahyu Chandra; Astawa, I Gede Santi (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2020)
The role of employees is needed to determine the success of a company. Performance appraisal performance is a way to measure the contribution made. One way to do an evaluation is by classifying the data. After the data is grouped into clusters, a ranking is done. Method used The Simple Additive Weighting (SAW) method is to find the weighted sum of the performance ratings for each alternative on all attributes. The criteria that will be used as a reference in making decisions are performance, presence and behavior. Very good performance was achieved by contract workers located in cluster 1, contract workers located in cluster 5 received a good rating, contract workers located in cluster 4 received a sufficient rating, contract workers located in cluster 4 received a bad predicate and contract workers located in cluster 3 get a very bad predicate. The purity method is used to measure the purity level of a cluster. The purity value obtained is 0.89 or 89%. Which indicates the accuracy value with the purity test is good because the purity value is close to 1